Histopathological patterns in atypical teratoid/rhabdoid tumors are related to molecular subgroup. (3rd May 2021) - Zin, Francesca; Cotter, Jennifer A.; Haberler, Christine; Dottermusch, Matthias; Neumann, Julia; Schüller, Ulrich; Schweizer, Leonille; Thomas, Christian; Nemes, Karolina; Johann, Pascal D.; Kool, Marcel; Frühwald, Michael C.; et al.
Abstract: Atypical teratoid/rhabdoid tumor (AT/RT) is a highly malignant tumor that may not only contain rhabdoid tumor cells but also poorly differentiated small‐round‐blue cells as well as areas with mesenchymal or epithelial differentiation. Little is known on factors associated with histopathological diversity. Recent studies demonstrated three molecular subgroups of AT/RT, namely ATRT‐TYR, ATRT‐SHH, and ATRT‐MYC. We thus aimed to investigate if morphological patterns might be related to molecular subgroup status. Hematoxylin‐eosin stained sections of 114 AT/RT with known molecular subgroup status were digitalized and independently categorized by nine blinded observers into four morphological categories, that is, "rhabdoid, " "small‐round‐blue, " "epithelial, " and "mesenchymal." The series comprised 48 ATRT‐SHH, 40 ATRT‐TYR, and 26 ATRT‐MYC tumors. Inter‐observer agreement was moderate but significant (Fleiss' kappa = 0.47; 95% C.I. 0.41‐0.53; p < 0.001) and there was a highly significant overall association between morphological categories and molecular subgroups for each of the nine observers ( p < 0.0001). Specifically, the category "epithelial" was found to be over‐represented in ATRT‐TYR ( p < 0.000001) and the category "small‐round‐blue" to be over‐represented in ATRT‐SHH ( p < 0.01). The majority of ATRT‐MYC was categorized as "mesenchymal" or "rhabdoid, " but this association was less compelling. The specificity of the category "epithelial" for ATRT‐TYR was highest and accounted for 97% (range: 88‐99%) whereas sensitivity was low [49% (range: 35%–63%)]. In line with these findings, cytokeratin‐positivity was highly overrepresented in ATRT‐TYR. In conclusion, morphological features of AT/RT might reflect molecular alterations and may also provide a first hint on molecular subgroup status, which will need to be confirmed by DNA methylation profiling.